Pengembangan e-modul interaktif berbasis gamifikasi pada pembelajaran teks fabel - Fatimah, Khusnul; Viono, Tono; Ambarwati, Ari (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
The change in the learning paradigm demands innovation in learning components. Electronic modules can encapsulate innovation regarding input, learning instruments, and facilities. Based on the needs analysis, fable text is essential because it can instill character. This research aims to develop a gamification-based interactive e-module to provide interactivity experience through games for students. The research method used is the Research and Development (R&D) method, with the development process using the ADDIE model (analyze, design, development, implementation, evaluation). The ADDIE model is systematic, easy, and has an iterative evaluation, so it is appropriate to be applied to develop modules. Media and material experts' results of the validation test stated that the module was categorized as valid. Based on the limited trial, it was found that students' responses to the e-module showed a very good category in terms of ease of use, attractiveness, language use, and media display. The results of the broad trial showed a number less than 0.05, so it can be stated that the Komiknesia e-module was proven effective in improving student learning outcomes.